Analysis of a physiotherapy program in a group of patients with multiple sclerosis. - Oliveira, Nayara Galvão; Bofi, Tânia Cristina; Barbatto, Lúcia Martins; Carvalho, Augusto Cesinando de (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Multiple sclerosis (MS) is a progressive disease that affects a population usually under 40 years of age. These people used to be advised to reduce their level of physical activity to reduce the risk of new outbreaks. On the other hand, groups of people with MS have been involved in therapeutic physical activity programs and achieved similar benefits to those obtained by healthy people. Objective: The aim of this study was to characterize the physical therapy procedures and analyze the efficiency of physiotherapy group in these individuals. Method: Participated in this quasi-experimental study, 04 participants (37.2±6 years, 7±3 years of injury, 22.8±3 kg/m2) with MS attending physiotherapy group in the CEAFIR FCT/UNESP. To characterize the functional capacity and motor skills of the Berg Balance Scale (BBS) and Six-minute walk test (6MWT) were used, the perceived quality of life was assessed by SF-36. The evaluations took place before starting the exercise protocol group and after 18 sessions. 18 sessions were filmed for description of physical therapy procedures used during physical therapy sessions in groups. For statistical analysis, GraphPad Prism 5 program (GraphPad Software Inc., San Diego, CA, USA) was used. Data normality was assessed using the Shapiro Wilk test and comparison of data was performed by paired t test (p<0.05). Results: There was a significant difference in body balance and functional ability of participants by BBS and by the 6MWT, respectively, in the comparison between the first assessment and the second assessment (p=0.01). There was no significant difference when comparing the hemodynamic parameters during the 6MWT and the perception of HRQoL compared between the two assessments (p>0.05). Conclusion: The physiotherapy program group for ME proved effective in improving and maintaining body balance and functional capacity of these participants.